Development and validation of an arthropod maceration protocol for zoonotic pathogen detection in mosquitoes and fleas. Issue 1 (5th June 2015) - Harrison, Genelle F.; Scheirer, Jessica L.; Melanson, Vanessa R.
ABSTRACT Arthropod‐borne diseases remain a pressing international public health concern. While progress has been made in the rapid detection of arthropod‐borne pathogens via quantitative real‐time (qPCR), or even hand‐held detection devices, a simple and robust maceration and nucleic acid extraction method is necessary to implement biosurveillance capabilities. In this study, a comparison of maceration techniques using five types of beads followed by nucleic acid extraction and detection were tested using two morphologically disparate arthropods, the Aedes aegypti mosquito and Xenopsylla spp. flea, to detect the zoonotic diseases dengue virus serotype‐1 and Yersinia pestis. Post‐maceration nucleic acid extraction was carried out using the 1‐2‐3 Platinum‐Path‐Sample‐Purification (PPSP) kit followed by qPCR detection using the Joint Biological Agent Identification and Diagnostic System (JBAIDS). We found that the 5mm stainless steel beads added to the beads provided in the PPSP kit were successful in macerating the exoskeleton for both Ae. aegypti and Xenopsylla spp. Replicates in the maceration/extraction/detection protocol were increased in a stepwise fashion until a final 128 replicates were obtained. For dengue virus detection there was a 99% positivity rate and for Y. pestis detection there was a 95% positive detection rate. In the examination of both pathogens, there were no significant differences between qPCR instruments, days ran, time of day ran, or operators.